Price premium for green open space and tree cover in the city of Buenos Aires - Zoloa, Juan Ignacio (2017)
Green areas provide aesthetic, recreational, social, and environmental benefits to surrounding communities. Local governments usually face many challenges while deciding on the protection of existing green space or the creation of new one. Understanding the direct economic impacts of green areas on neighboring properties can help with the economic and political decision-making. The aim of this study is to estimate individuals’ valuations of green space in a highly densely populated city like Buenos Aires, Argentina. This paper applies spatial hedonic price models to obtain the value of urban green areas, urban trees, and tree cover. The results show a price premium for all green variables, and that not all trees are valued equally. Also, results suggest that more diversity increase the monetary value of a property. Results from this study could help inform the debate on the true opportunity costs of allowing construction over unused parcels of land in Buenos Aires.